2022
DOI: 10.1055/a-1952-1159
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Stenosis and Stroke: Medicines, Stents, Surgery—“Wait-and-See” or Protect?

Abstract: no abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 132 publications
(476 reference statements)
0
7
0
Order By: Relevance
“…Despite a significant carotid reopening rate with balloon angioplasty alone (84%), the 90-day mRS £2 was only 39%. This is in contrast to the 91.7% in our treatment cohort (Figure 3), where sealing of the culprit lesion and lumen reconstruction was routinely performed novel micronet-covered stents to sequestrate the plaque and prevent further plaque-related events [4,25,28,37,38], suggesting that culprit lesion effective exclusion and optimal lumen reconstruction may be clinically fundamental in AIS-CA.…”
Section: E938549-7mentioning
confidence: 71%
See 2 more Smart Citations
“…Despite a significant carotid reopening rate with balloon angioplasty alone (84%), the 90-day mRS £2 was only 39%. This is in contrast to the 91.7% in our treatment cohort (Figure 3), where sealing of the culprit lesion and lumen reconstruction was routinely performed novel micronet-covered stents to sequestrate the plaque and prevent further plaque-related events [4,25,28,37,38], suggesting that culprit lesion effective exclusion and optimal lumen reconstruction may be clinically fundamental in AIS-CA.…”
Section: E938549-7mentioning
confidence: 71%
“…Intracranial LVO MT [ 19 ] was performed in tandem lesions. The culprit CA lesion sequestration was performed using micronet-covered stents [ 4 , 25 , 28 , 37 , 38 ]. Functional status was routinely assessed at 90 days.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that carotid artery stenting or trans-carotid stent-assisted revascularization, with their inherent "final" confirmation of lesion severity by intra-arterial angiography (standard of reference), would probably have resulted in deferring any interventional management because in this study patient catheter quantitative angiography (cQA, NASCET method) revealed LICA stenosis severity of 47%. Medical therapy was maximized to reduce stroke risk [3,25,26], and the patient is monitored yearly in a certified DUS lab for potential stenosis progression [3,4,6] along with imaging and clinical observation for de novo presence of other increased stroke risk characteristics [3,4,6,25,26]. A documented increase in stenosis severity would trigger the NeuroVascular Team to re-consider recommended management, which would involve the patient's opinion (based on complete information on treatment options [26]) in the decision-making process showing the narrowest lumen diameter 3 measurements were performed and the average %DS was taken for further analysis.…”
Section: Intra-arterial Angiographymentioning
confidence: 99%
“…Medical therapy was maximized to reduce stroke risk [3,25,26], and the patient is monitored yearly in a certified DUS lab for potential stenosis progression [3,4,6] along with imaging and clinical observation for de novo presence of other increased stroke risk characteristics [3,4,6,25,26]. A documented increase in stenosis severity would trigger the NeuroVascular Team to re-consider recommended management, which would involve the patient's opinion (based on complete information on treatment options [26]) in the decision-making process showing the narrowest lumen diameter 3 measurements were performed and the average %DS was taken for further analysis.…”
Section: Intra-arterial Angiographymentioning
confidence: 99%